Performance Comparison of Ion Lithium Batteries and Lead Acid Batteries in Electrical Energy Storage Systems - M.Si, musrawati ST; Faridah, Faridah; Sriwati, Sriwati (Universitas Pancasakti, 2026)
Enrekang Regency, which is mostly mountainous and has an increasing need for a reliable electrical energy storage system along with the development of renewable energy technologies such as solar panels and wind turbines. Two types of batteries commonly used are ion lithium batteries and lead acid batteries. Research Objectives To determine the effectiveness of the performance of ion lithium batteries and lead acid batteries and to determine the relative energy storage capacity of these two types of batteries and to determine whether one of them has an advantage in greater storage capacity. The method used in this study is This study uses a comparative descriptive approach with a literature study method (library research) and quantitative data analysis. The aim is to compare the technical performance of two types of batteries based on relevant and valid secondary data. The results of this study indicate that ion lithium batteries have the advantage of lasting a long time when discharged with a load, ion lithium batteries last for 8 hours 43 minutes, compared to lead acid which only lasts for 7 hours 48 minutes, this data collection is carried out by charging and discharging tests, life cycle tests, self-tests, and safety tests